GATE 2023: Computer Science & Information Technology - Made easy (Made easy pub, 2022)
GATE 2023: Computer Science & Information Technology / Made easy. -- New Delhi: Made easy pub, 2022 153.94004 M181e16 16th ed. No. of Copies : 1